Qualidade fisiológica de sementes de feijão e soja armazenadas em atmosfera controlada sob diferentes temperaturas - Berghetti, Magno Roberto Pasquetti (2024)
Seed storage is one of the crucial steps in agricultural production, because it has a great influence on the expression of the plants' productive potential. Although there are several storage technologies, much of the seeds physiological quality is still lost due to inadequate conditions used during storage. The main objective of the research was to evaluate the effect of low oxygen partial pressures (pO2) and high carbon dioxide partial pressures carbon dioxide (pCO2), in controlled atmosphere storage, combined with different temperatures on the maintenance of the physiological potential of bean and soybean seeds and their effects on productivity. In the 2020/21 harvest, bean seeds from the Fepagro Triunfo and Fepagro Garapiá cultivars and soybean seeds from the NA 5909 RR cultivar were stored for eight months under the following conditions: [1] Ambient; [2] 1.0 kPa O2 + 0.04 kPa CO2; [3] 1.0 kPa O2 + 15.0 kPa CO2 at temperatures of 10, 15, 20 and 25 °C. In the 2021/22 harvest, seeds of the cultivar F. Triunfo and soybeans of the cultivar NA 5909 RR were stored for six months under the following conditions: [1] Ambient; [2] 1.0 kPa O2 + 0.0 kPa CO2; [3] 3.0 kPa O2 + 0.0 kPa CO2 and [4] 5.0 kPa O2 + 0.0 kPa CO2 at temperatures of 10, 15 and 20 °C. The evaluations carried out after seed storage were: Water content, mass loss, electrical conductivity, standard germination test, seedling length, seedling dry mass, activity of the enzymes guaiacol peroxidase and superoxide dismutase and hydrogen peroxide content. After sowing, the following parameters were evaluated: field emergence, plant height, leaf area index and productivity. In general, in the two years of evaluation, seeds stored at temperatures of 10 °C using a controlled atmosphere (CA) maintained the highest physiological quality during storage among the variables evaluated. Bean and soybean cultivars stored under low oxygen (1.0 kPa O2) showed increased productivity compared to the Ambient condition and the use of higher temperatures during storage, such as 15, 20 and 25 °C for soybean cv. NA5909 RR and bean cv. F. Garapiá and at 25 °C beans cv. F. Triunfo showed less physiological quality maintenance compared to seeds stored at 10°C. There was no additive effect of high concentrations of CO2 to the low level of O2 in the silo atmosphere on maintaining seed quality.